Thermomechanical behavior of flexible composite substrate for microelectronic packaging - Zuñega, Jonee Christine (Animo Repository, 2003)
The warpage of a flexible composite substrate attached to a metal frame carrier during post curing process was assessed by finite element modeling. Both small displacement analysis (SDA) using ANSYS and large displacement analysis (LDA) using ABAQUS software were tried. The flexible substrate was modeled as a composite laminate and stress-strain relations were based on assumption of isotropic, segmentally-heterogeneous property and plane stress condition. Validation of Finite Element Analysis (FEA) results were carried out using Shadow Moire experiments as well as oven curing runs. To investigate effects on the warpage by such substrate-related factors as layer symmetry, use of copper panels and use of frame carrier, a 23 factorial experimental design was utilized to estimate the maximum displacement/thickness response at different combinations of the three factors as predicted by FE-LDA. Results showed that the effects of the three factors are far from additive but rather dictated by major interactions, with the most pronounced interaction involving the layer symmetry and the frame carrier. Results of the validation runs showed that FE-LDA estimates were more realistic than those of FE-SDA since the maximum average displacement/thickness of 60.6 for FE-LDA was between the average for Shadow Moire data (57.5) and oven curing data (72.5) with FE-SDA giving estimates which were unrealistically high (125). The material component of the flexible substrate which contributed the greatest amount of displacement is attributed to the photoresist layer rather than the polyimide and metal layers considering it has the highest coefficient of thermal expansion.